2022
DOI: 10.12962/j24433527.v15i1.11416
|View full text |Cite
|
Sign up to set email alerts
|

Analisa Kualitas Pelayanan di Departemen Teknik Kimia Industri, Fakultas Vokasi ITS Surabaya dalam perspektif Higher Education Performance (HEdPerf)

Abstract: The purpose of this study was to measure the performance of service quality by using students' perceptions of service quality performance at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…They identified 20 attributes with negative gaps, indicating areas for improvement in the program (Febriani et al, 2022). Research by (Purwanto et al 2022) using Hedperf and HIEDQUAL to measuring the quality of services at the University showed that items in this study did not meet customer expectations, as demonstrated by negative scores in SERVQUAL analysis. The use of this method allows a comprehensive assessment of education quality, taking into account factors such as teaching, facilities, extracurricular activities, and social contexts.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…They identified 20 attributes with negative gaps, indicating areas for improvement in the program (Febriani et al, 2022). Research by (Purwanto et al 2022) using Hedperf and HIEDQUAL to measuring the quality of services at the University showed that items in this study did not meet customer expectations, as demonstrated by negative scores in SERVQUAL analysis. The use of this method allows a comprehensive assessment of education quality, taking into account factors such as teaching, facilities, extracurricular activities, and social contexts.…”
Section: Discussionmentioning
confidence: 74%
“…The attributes in this quadrant are the strengths of the campus and these attributes must be an advantage and must be maintained. The results of the study (Purwanto et al, 2022) found that reputation is a priority factor that must be considered.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, it is required to organize marketing activities and promotional programs to inform students. Purwanto, Noor, and Kusumawati (2020) concluded that the university maintains its services at a sufficient level in terms of reputation. Since service quality in the reputation dimension is perceived at a sufficient level, it can be tried to increase the quality perceptions of the students by making improvements in this dimension.…”
Section: Ii1 Quality Measurement In Hesmentioning
confidence: 99%